Multinomial logit death forecasting model - Jakaitienė, Audronė (Lietuvos matematikos rinkinys, 1999)
The multinomial regression logit model is analyzed. The algorithms and software are made for this model in order to get estimation of parameters. Calculations are made using generated population of 1000 cases.